2021
DOI: 10.1002/pmic.202000310
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the structures and proteoform profiles of the complement proteins C6 and C7

Abstract: The human complement system provides a first line of defence against pathogens.It requires a well-orchestrated sequential assembly of an array of terminal complement components (C5, C6, C7, C8, and C9), ultimately forming the membrane attack complex (MAC). Although much information about MAC assembly is available, the structure of the soluble C7 has remained elusive. The complement proteins C7 and C6 share very high sequence homology and exhibit several conserved domains, disulphide bridges, and C-mannosylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…C6 also has a partially occupied C‐mannosylation site at TSR2 residue W69 in a noncanonical GPWSDCDP sequence [11]. This modification was not present in the C‐mannosylated crystal structure in the PDB and C‐mannosylated W69 is the less abundant proteoform (30%) [28]. Nonetheless, if approximately a third of circulating C6 monomers have this modification present, it may still influence the interactions or stability of C6 in the complement system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C6 also has a partially occupied C‐mannosylation site at TSR2 residue W69 in a noncanonical GPWSDCDP sequence [11]. This modification was not present in the C‐mannosylated crystal structure in the PDB and C‐mannosylated W69 is the less abundant proteoform (30%) [28]. Nonetheless, if approximately a third of circulating C6 monomers have this modification present, it may still influence the interactions or stability of C6 in the complement system.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the variable occupancy of the C‐mannosylation site on C9 can subtly influence the assembly of C9 monomers, or perhaps their interactions with pathogen membranes, remains to be seen. The heterogeneity of C‐mannosylation on human plasma‐derived C6 has been demonstrated [28] and these data showed that the crystallized proteoform was the most abundant and thus provides a strong representation of C‐mannosylation in soluble, monomeric C6. The variable occupancy of C‐mannosylation sites in the three TSR domains contributes to the overall heterogeneity of soluble C6 and may be particularly influential in the assembled MAC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that almost all complement proteins can bear sialylated glycans [82][83][84] . Factor H, which inhibits the cascade, binds α2,3 sialylation on host-cells, a critical aspect of self-recognition 85 .…”
Section: Discussionmentioning
confidence: 99%
“…nearly obsolete but also decreases the required protein amounts as well as undesired over-length cross-links. In contrast to classical in-solution XL-MS workflows, IGX-MS allows the differentiation of conformation-and interaction-specific distance restraints as it has been shown for various mitochondrial complexes but also for plasma protein complexes, the mitotic checkpoint complex (MCC) as well as for different assemblies of the archaeal ammonia monooxygenase (176)(177)(178)(179). IGX-MS seems specially promising for future modeling studies that aim at characterizing cooccurring protein complexes with different stoichiometries or assembly states.…”
Section: Combining Xl-ms and Cp-ms For The Structural Analysis Of Pro...mentioning
confidence: 99%